The Aspergillus nidulans rcoA Gene Is Required for veA-Dependent Sexual Development - Todd, Richard B. (Copyright © 2006 by the Genetics Society of America, 2006)
The Aspergillus nidulans rcoAΔ mutant exhibits growth and developmental defects. We show that the rcoAΔ mutant lacks cleistothecia and is self-sterile. In crosses with wild-type strains, rcoAΔ nuclei do not contribute to the cleistothecial walls. Furthermore, sexual development resulting from veA overexpression is rcoA dependent, indicating that rcoA lies downstream of veA in the sexual development pathway.